Double burden of malnutrition and associated factors among mother–child pairs at household level in Bahir Dar City, Northwest Ethiopia: community based cross-sectional study design - Mekonnen, Solomon; Birhanu, Dereje; Menber, Yonatan; Gebreegziabher, Zenebe Abebe; Belay, Mahider Awoke (Frontiers in Nutrition, 2024)
Introduction The double burden of malnutrition refers to the simultaneous presence of under nutrition and overweight, obesity, or diet-related non-communicable diseases which might occur at the population, household, and individual level. The simultaneous presence of overweight/obese mothers with undernourished children in the same household, as well as overweight children with underweight mothers, holds particular significance. This phenomenon primarily impacts low-income and middle-income countries. The prevalence of double-burden malnutrition at the household level has increased significantly in sub-Saharan African countries. However, there is limited knowledge regarding the extent and factors associated with the double burden of malnutrition among mother–child pairs in Ethiopia. Consequently, the objective of this study was to assess the prevalence and determinants of the double burden of malnutrition among mother–child pairs at the household level in Bahir Dar City, Ethiopia. Method In the year 2021, a community-based cross-sectional study design was employed among 702 mother–child pairs in Bahir Dar City from February 28 to March 23. A multistage sampling technique was used to identify study participants who were interviewed using an interviewer-administered questionnaire. The nutritional status of children was evaluated using WHO Anthro Software. To determine the strength of the association, multivariable logistic regression analysis was performed, and adjusted odds ratios with their respective 95% confidence intervals were computed. Results The prevalence of the double burden of malnutrition among mother–child pairs was 14.5% (95% CI: 12.8, 15.7%